Women’s land tenure security: A conceptual framework - Doss, Cheryl; Meinzen-Dick, Ruth S. (2018)
This paper develops a conceptual framework around women’s land tenure security and the factors that influence it. It is an attempt to develop some shared definitions and concepts to facilitate aggregation of the lessons from individual analyses and case studies by outlining the key elements that may be related to women’s tenure security. Many studies identify one or two of the elements without discussing how the others may be related. Studies considering how policies or projects may change tenure security in a particular context often do not provide sufficient information on the regional or national context to allow comparisons across countries. This framework outlines the key dimensions of the context that may be relevant. In addition, because women’s tenure security is not static, this framework identifies the types of factors that may change women’s tenure security, both to strengthen it and to undermine it.